Хмарна система для контролю «розумного будинку» на базі RASPBERRY PI І Z-WAVE технології - Романішин, В. В. (ХНУРЕ, 2020)
The given work is devoted to hardware and software of home automation system. The main function of the home automation systems is allow homeowners to monitor and control their home from remote locations. Proposed architecture solution are based on wireless data transfer protocol. The article describes system, which consists of several special separate components, main principles of communications between components and software used by those modules.
Keywords: розумний будинок; Z-Wave мережа; контролер